2018
DOI: 10.3126/jbss.v2i1.22827
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Green Banking Practices on Bank’s Environmental Performance: Empirical Evidence from Kathmandu valley

Abstract: The research paper aims to analyze the impact of green banking practices on bank’s environmental performance in Nepal. The casual relational research design has been adopted in the study. The simple and stepwise multiple regression analysis have been performed to accomplish the objective of the research. The research paper follows cross-sectional qualitative research with descriptive outcome. The Chronbach’s Alpha has been used to analyze the reliability of instruments and data. The 189 samples have been colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 4 publications
7
36
1
1
Order By: Relevance
“…The study further showed that GB practices (environmental training of employees, energy-efficient practices, green policy and overall green projects) positively affected banks' environmental performance in city of Coimbatore, India. Similarly, Risal and Joshi [28] studied the impact of GB practices on banks' environmental performance in Nepal using multiple regression analysis. The study concluded that environmental training, banks' green policy and energy-efficient equipment significantly influenced the environmental performance of banks, contrary to the customer-related practices' (green financing and green projects), the effects of which were statistically insignificant.…”
Section: Green Banking Practices and Banks' Environmental Performancementioning
confidence: 99%
See 4 more Smart Citations
“…The study further showed that GB practices (environmental training of employees, energy-efficient practices, green policy and overall green projects) positively affected banks' environmental performance in city of Coimbatore, India. Similarly, Risal and Joshi [28] studied the impact of GB practices on banks' environmental performance in Nepal using multiple regression analysis. The study concluded that environmental training, banks' green policy and energy-efficient equipment significantly influenced the environmental performance of banks, contrary to the customer-related practices' (green financing and green projects), the effects of which were statistically insignificant.…”
Section: Green Banking Practices and Banks' Environmental Performancementioning
confidence: 99%
“…The initial measurement items of BERP, BORP, BCRP and BPRP were formulated based on the related studies of refs. [16,28,29]. Furthermore, three items were developed from past studies [1,5] to measure the sources of green financing.…”
Section: Instruments Developmentmentioning
confidence: 99%
See 3 more Smart Citations